Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter 1 - Equations and Inequalities - 1.3 Complex Numbers - 1.3 Exercises: 55

Answer

$(2+i)(3-2i)=8-i$

Work Step by Step

$(2+i)(3-2i)$ Evaluate the product by multiplying each term of the first factor by every term of the second factor: $(2+i)(3-2i)=6-4i+3i-2i^{2}=...$ Substitute $i^{2}$ by $-1$ and simplify: $...=6-4i+3i-2(-1)=6-i+2=8-i$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.